Enhanced megaproject management systems in the LNG industry: A case study from Qatar - Salman H. Ashkanani (17317087) (2023)
Despite the development of several industrial Liquefied Natural Gas (LNG) megaprojects worldwide, minimal literature on LNG megaprojects is available in the non-proprietary public domain and academia, with the consequent lack of availability of practical tools, guidelines, and benchmarks for the use of professionals engaged in developing and managing LNG megaprojects. Cognizant of this fact, the authors have attempted a study of standard project management systems to explore practical ways to meet the unique needs of LNG megaprojects management and systematically assimilate lessons learned to replicate successes and avoid failures. Considering the complexity of the LNG value chain, a management system approach has been adopted. Combining academic and industrial knowledge, this study identifies nine significant areas that, when improved, should enhance the management of LNG megaprojects throughout their lifecycle — from initiation to handover for operation. With hundreds of billions of dollars invested in current LNG projects, even minor improvements can be worth billions. This study also addresses the challenges of megaprojects development, gaps that need to be overcome, and the importance of quality and lessons learned. Finally, although the focus of this study is the management of LNG megaprojects, it is expected that many improvements identified here would find relevance in managing large and complex projects, even in other industrial sectors. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2022.12.030